EU ACCESSION IMPACTS ON THE COMPARATIVE ADVANTAGES IN AGRICULTURAL TRADE: ROMANIAS CASE - Rusali, Mirela (Economics of Agriculture, 2012)
The research aims at evaluating the accession impacts on Romanias agriculture by analysing the comparative advantages in trade relations with EU. The method used the calculation of the trade specialization degree index constructed from the original Lafay index and adapted on the agricultural sector. While providing a rank of products by their level of specialization on the international market, the research results indicate a decrease of the specialization level and a loss in the trade diversification of the Romanian products. The assessments reveal that certain products previously expressing an export potential, have suffered in the post-accession period an important decline in their commercial specialization: such is the case of live animals and animal products, which, although still have positive trade balance, the net export amounts registered signifcant declines. The results identifed similar loss for oilseeds, milk and dairy products.